2016
DOI: 10.4254/wjh.v8.i32.1370
|View full text |Cite
|
Sign up to set email alerts
|

Changes in cellular proliferation and plasma products are associated with liver failure

Abstract: AIMTo study the differences in immune response and cytokine profile between acute liver failure and self-limited acute hepatitis.METHODSForty-six patients with self-limited acute hepatitis (AH), sixteen patients with acute liver failure (ALF), and twenty-two healthy subjects were involved in this study. The inflammatory and anti-inflammatory products in plasma samples were quantified using commercial enzyme-linked immunoassays and quantitative real-time PCR. The cellular immune responses were measured by proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…However, these structures containing mtDNA are able to provoke a rapid type I interferon (IFN-I) production in peripheral blood mononuclear cells, suggesting that lymphocytes and monocytes use mtDNA as a rapid signaling molecule to communicate danger 21 . Interestingly, mtDNA being enriched in unmethylated cytosine-phosphate-guanine (CpG) dinucleotide motifs similar to bacterial and viral DNA could provoke IL-10 secretion 21,22 , and transforming growth factor beta (TGF-β) release 23 . IL-10 is known to be an anti-inflammatory cytokine 24 , and TGF-β mediates the suppression of macrophage-directed inflammation, reducing TNF-α release 25 .…”
Section: Introductionmentioning
confidence: 99%
“…However, these structures containing mtDNA are able to provoke a rapid type I interferon (IFN-I) production in peripheral blood mononuclear cells, suggesting that lymphocytes and monocytes use mtDNA as a rapid signaling molecule to communicate danger 21 . Interestingly, mtDNA being enriched in unmethylated cytosine-phosphate-guanine (CpG) dinucleotide motifs similar to bacterial and viral DNA could provoke IL-10 secretion 21,22 , and transforming growth factor beta (TGF-β) release 23 . IL-10 is known to be an anti-inflammatory cytokine 24 , and TGF-β mediates the suppression of macrophage-directed inflammation, reducing TNF-α release 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Inclusion criteria included the presence of coagulopathy (INR ≥ 1.5) and encephalopathy score above II, according to O'Grady et al [ 21 ] and as described previously [ 7 , 22 , 23 ]. Clinical details of the study population are shown in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…ALF can be induced by viral infections and toxicity promoted by drug abuse or alcoholism. In Brazil, viral infections are responsible for the majority of ALF cases, including viral hepatitis viruses such as hepatitis A virus (HAV) and hepatitis B virus (HBV), as well as coinfections related to hepatitis C virus (HCV), HIV, Epstein-Barr virus, and CMV [ 5 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…High serum proinflammatory cytokines levels have been reported (21,22) and are related to the development of multiorgan dysfunction (23). Pro-inflammatory cytokines are also involved in the systemic inflammatory response syndrome pathophysiology (24).…”
Section: Discussionmentioning
confidence: 99%
“…ALF is characterized by massive necroinflammation of liver tissue and is associated with high mortality (21,22). High serum proinflammatory cytokines levels have been reported (21,22) and are related to the development of multiorgan dysfunction (23).…”
Section: Discussionmentioning
confidence: 99%